THE DISCOURSE OF SCIENTIFIC APPROACH IN THE STUDY OF FIQH AL-HADITH: APPLICATIONS OF HEGEL'S DIALECTICS - Prayogi, Ananda (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2022)
In the last decade, a new approach has been developed called the scientific approach to understanding hadith (fiqh al-hadith). Interestingly, there is a theory that states that everything that is tested through a scientific approach has a principle that can always be falsified. From this, the assumption arises that if the truth of the hadith is already based on scientific theory, but later there is a revision that causes the theory to be falsified, then this will actually drop the validity of the hadith itself. Hegel's philosophical theory is a method that is considered appropriate to resolve these pros and cons. This study aims to answer how Hegel's dialectical theory works and its urgency in research. In addition, the pros and cons in the discourse of the scientific approach and how Hegel's dialectics can be applied within the scope of the study of fiqh al-hadith. This study uses a literature study method with a qualitative-descriptive approach. As a result, Hegel's dialectic turns out to be applicable in problems that arise from the contradiction of two things. Furthermore, the pros and cons in the scientific approach arise from efforts to understand the hadith and efforts to strengthen its validity. The pros and cons, after being analyzed using Hegel's dialectics, turned out to produce several solutions. First, only hadiths that explicitly mention natural phenomena can use a scientific approach. Second, science is only a support, not a basis for validity. Third, the hadith studied must always be positioned as an undeniable revelation from Allah.AbstrakPada dekade belakangan, berkembanglah pendekatan baru yang disebut pendekatan saintifik untuk memahami hadis (fiqh al-hadis). Menariknya, terdapat teori yang menyebutkan bahwa segala sesuatu yang diuji melalui pendekatan saintifik memiliki prinsip selalu dapat difalsifikasi. Dari sini, timbul asumsi jika kebenaran hadis yang sudah dilandasi dengan teori sains jika kemudian terdapat revisi yang menyebabkan teori tersebut difalsifikasi, maka hal ini justru akan menjatuhkan validitas hadis itu sendiri. Teori filsafat Hegel merupakan metode yang dianggap tepat untuk menyelesaikan pro-kontra ini. Penelitian ini bertujuan untuk menjawab bagaimana teori dialektika Hegel bekerja serta urgensinya dalam penelitian. Selain itu, pro-kontra dalam diskursus pendekatan sains serta bagaimana dialektika Hegel dapat diterapkan dalam ruang lingkup kajian fiqh al-hadis. Penelitian ini menggunakan metode studi pustaka dengan pendekatan kualitatif-deskriptif. Hasilnya, dialektika Hegel ternyata dapat diterapkan dalam masalah yang timbul dari pertentangan dua hal. Selanjutnya, pro-kontra dalam pendekatan saintifik timbul dari upaya untuk memahami hadis dan upaya untuk menguatkan validitasnya. Pro-kontra tersebut setelah dilakukan analisis menggunakan dialektika Hegel, ternyata menghasilkan beberapa pemecahan. Pertama, hanya hadis yang menyebutkan fenomena alam secara eksplisit yamh dapat menggunakan pendekatan saintifik. Kedua, sains hanya sebagai pendukung, bukan landasan validitas. Ketiga, hadis yang dikaji harus selalu diposisikan sebagai wahyu dari Allah yang tidak dapat dibantah